Novel distributed control for multi-agent systems: Application to a quadcopter formation - Nguyen, M. Xuan (Vietnam Journal of Science and Technology, 2026)
Multi-agent systems (MAS) are well-known for overweighting single agents that exhibit several complex tasks. This paper introduces a novel approach to modeling and controlling an MAS employing a directed and switchable topology. The interaction dynamics of the MAS are described through a mass–spring system, where individual agents are modeled as point masses and their relative positions are represented by virtual elastic links that produce coordination forces. A notion of formation equilibrium is introduced to describe the steady-state configuration of the network, which is characterized via the underlying interaction forces. By examining these equilibrium conditions, a distributed control strategy is constructed to guarantee convergence toward the prescribed geometric configuration. The performance and validity of the proposed method are verified through comprehensive simulation studies.